PERKEMBANGAN PENGUASAAN ANTARIKSA (SPACE) CINA DAN DEFENCE DILLEMA: PERANG DINGIN KEDUA ANTARA AS DAN CINA - Andhini . (Jurnal Ilmu dan Budaya, 2016)
The focus of this article is to discuss the relationship between China's defense policy and US responds. The theories applied are defense dilemma and the power-security dilemma. China's economic and military progress pose a threat to other countries, especially for the US’s existence. China is increasing its current space capabilities. In 2007, China has successfully tested anti-satellite (ASAT). Chinese’s current space capabilities could destroy satellites owned by US. Therefore, Obama issued a policy to divert the space program to the PPP (private-public partnership). This program would be fully funded by the government and the US government cooperates with private companies to increase the exploration of space. Both countries suspect each other doing spies through space.